2018
DOI: 10.1016/j.marpol.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Occupational safety in aquaculture – Part 2: Fatalities in Norway 1982–2015

Abstract: This article presents an overview of reported fatalities in the Norwegian aquaculture industry focusing on the production of Atlantic salmon and trout, which dominate the fish farming industry in Norway. The data on fatalities from 1982-2015 are registered by SINTEF Ocean, which is the only data source available. The fatality data set includes information on the incidents leading to fatalities, activities conducted at the time of fatalities, and the time of year the fatalities were registered. The article disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…68 In a second report, Holen et al (2017) reported 34 fatalities in Norwegian aquaculture from 1982 to 2015, with most fatalities caused by loss of vessel (n = 15), man overboard (n = 5), and blow from an object (n = 6). 69 The authors suggested that seafaring vessel use and crane use represent critical intervention points for future worker safety interventions. Both of these analyses conclude that marine aquaculture work in Norway poses many occupational safety hazards, and that aquaculture work is second only to wild fisheries regarding the level of occupational risk.…”
Section: Us Aquaculture Sectormentioning
confidence: 99%
“…68 In a second report, Holen et al (2017) reported 34 fatalities in Norwegian aquaculture from 1982 to 2015, with most fatalities caused by loss of vessel (n = 15), man overboard (n = 5), and blow from an object (n = 6). 69 The authors suggested that seafaring vessel use and crane use represent critical intervention points for future worker safety interventions. Both of these analyses conclude that marine aquaculture work in Norway poses many occupational safety hazards, and that aquaculture work is second only to wild fisheries regarding the level of occupational risk.…”
Section: Us Aquaculture Sectormentioning
confidence: 99%
“…Juvenile trout and salmon are produced in smolt tubs with fresh water on land (with 1 death at this stage), and the grow-out occurs in sea-based net cages suspended from circular plastic collars (with 33 deaths at this stage): 15 of which involved vessel loss at sea, 6 resulted from contact with an object on the vessel, 5 from FOB, and 4 from diving (one of which occurred onshore when the diver was trapped in a drain pipe) [26]. These results are appropriate for onshore GoM operations but differ regarding current shell fish operations in the GoM.…”
Section: Non-gom Fatality Studiesmentioning
confidence: 99%
“…These operations require work vessels with cranes, winches, and arrangements to secure the equipment that is undergoing maintenance. An analysis of serious injuries and fatalities shows that blows from an object, entanglements and crush, and man over board are the most common modes of injuries and causes for fatalities [5,48]. Equipment such as cranes, winches, the net cage, and work vessels, used in operations where subcontractors are involved, are often involved in these types of injuries.…”
Section: Steps 12 and 13 Identify Hazards And Develop Safety Requirementsmentioning
confidence: 99%